2008
DOI: 10.1021/jm701098w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Series of Naphthamides as Potent, Orally Active Vascular Endothelial Growth Factor Receptor-2 Tyrosine Kinase Inhibitors

Abstract: We have previously shown N-arylnaphthamides can be potent inhibitors of vascular endothelial growth factor receptors (VEGFRs). N-Alkyl and N-unsubstituted naphthamides were prepared and found to yield nanomolar inhibitors of VEGFR-2 (KDR) with an improved selectivity profile against a panel of tyrosine and serine/threonine kinases. The inhibitory activity of this series was retained at the cellular level. Naphthamides 3, 20, and 22 exhibited good pharmacokinetics following oral dosing and showed potent inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Weiss and coworkers prepared another series of naphthamides as potent and selective inhibitors of VEGFR-2 [31]. Three of them (26, 27, 28) exhibited good pharmacokinetics following oral dosing and showed potent inhibition of VEGF-induced angiogenesis in the rat cornea.…”
Section: Antiangiogenic Agents Of Quinoline Typementioning
confidence: 99%
“…Weiss and coworkers prepared another series of naphthamides as potent and selective inhibitors of VEGFR-2 [31]. Three of them (26, 27, 28) exhibited good pharmacokinetics following oral dosing and showed potent inhibition of VEGF-induced angiogenesis in the rat cornea.…”
Section: Antiangiogenic Agents Of Quinoline Typementioning
confidence: 99%
“…A dataset of 82 compounds, which covered nearly four log units (pIC 50 = 5.8-9.7) for their inhibitory activity, was taken from the published KDR inhibitors [33][34][35]. The structures and their inhibitory activities are listed in Table 1.…”
Section: Datasetmentioning
confidence: 99%
“…Up to now, there are still a lot of researches focusing on the development of novel inhibitors of KDR [25][26][27][28][29][30][31][32]. Recently, a novel series of KDR inhibitors which can selectively inhibit KDR with high inhibitory activities reported by Harmange et al [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, types of atoms were assigned and grid representation of 3EWHOK was prepared (AutoGrid4 25 ). 3EWHOK template was validated by docking (AutoDock 4.2, TSRI) 25 with the six active inhibitors: K11, AAX, GIG, LIF, 887 and 900 from PDB ID: 3EWH 1 , 1Y6B 26 , 2OH4 27 , 1YWN 28 , 3B8R 2 and 3B8Q 2 , respectively and all docked poses showed the same configuration as those in the corresponding crystal structures with RMSD less than 2 Å. These results indicated that 3EWHOK was a good VEGFR-2 model for in silico experiment.…”
mentioning
confidence: 99%